KETERDIDIKAN PEREMPUAN DAN WACANA KESETARAAN DALAM NOVEL INDONESIA PRA-BALAI PUSTAKA - Yulianeta, Yulianeta (Jurnal Pendidikan Bahasa dan Sastra, 2018)
This research rests on the phenomenon that literary works are not born from cultural vacuum and social emptiness. The pre-Balai Pustaka Indonesian novels mark the public's awareness of the importance of education so that it cannot be separated from its social cultural system. The issue of the importance of women's education and equality discourse has been spawned in pre-Balai Pustaka Indonesian novels. This is important to be reflected as an effort to enrich the literary treasures of Indonesia that often side-stepped pre-Balai Pustaka literary works. Three pre-Balai Pustaka Indonesia novels that raise issues of women's education and equality discourse show the concern of Indonesian authors on issues related to women's education. This research seeks to explore the discourse of equality in three pre-Balai Pustaka Indonesian novels buried in the course of Indonesian literature. Therefore, feminist literary criticism and gender perspective are used. The results of this study contribute to the world of Indonesian literature, especially the activities of Indonesian literary criticism that reflect the presence of pre-Balai Pustaka Indonesia novels for the development of literary criticism in the present time and the future.